Tunnel of Bones - Schwab, Victoria (New York : Scholastic Press, 2019)
Now in Paris with her parents who are filming their TV show about the world's haunted cities, Cassidy Blake (who can see ghosts) and her friend Jacob (who is a ghost) are alert for trouble, especially when the filming takes them into the underground Catacombs, the empire of the dead, where Cassidy accidentally awakens a powerful poltergeist spirit--one whose mystery she must solve before his power in unleashed on the whole city.
Keywords: Ghost stories; Psychics -- Juvenile fiction; Haunted places -- Juvenile fiction; Catacombs -- Juvenile fiction; Ghost television programs -- Juvenile fiction; Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Paranormal fiction; Ghosts -- Fiction; Psychics -- Fiction; Haunted places -- Fiction; Catacombs -- Fiction; Ghost television programs -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Parapsychology -- Fiction; Paris (France) -- Juvenile fiction; France -- Juvenile fiction; Paris (France) -- Fiction; France -- Fiction